Don't ever touch me (again) - Farris, Dionne; Sony Music Entertainment (New York : Sony Music Entertainment, 1995)
Dionne's 2nd single is a song about lost love and heartache. Taken from the album'Wild Seed - Wild Flower' which is much influenced by the sounds of rock, R&B, blues and folk.
CD 1 : Radio edit -- Long version -- Live version.
Koleksi Khas Wiramanja.
Title from disc label.
Keywords: Songs, English